Application of attenuated total reflection infrared spectroscopy in the study of Peruphasma schultei defensive secretion. Issue 3 (2007) - Mcleod Mcleod, Michael P. Michael P.; Dossey Dossey, Aaron T. Aaron T.; Ahmed Ahmed, M. Khalique M. Khalique
Abstract : In this short communication, we present the first Fourier Transform Infrared Absorbance (FT-IR) study of peruphasmal; a defensive secretion from Peruphasma schultei . The spectral data collected are representative of the natural product structure proposed by Dossey et al. This study demonstrates the viability of FT-IR as another tool in the physical and biological chemist's repertoire for use in determining important structural characteristics from minute amounts of available sample.